'All shall be well' : explorations in Universalism and Christian theology from Origen to Moltmann - MacDonald, Gregory (James Clarke & Co, 2011)
Universalism runs like a slender thread through the history of Christian theology. Over the centuries Christian universalism, in one form or another, has been reinvented time and time again. In this book an international team of scholars explore thediverse universalisms of Christian thinkers from the Origen to Moltmann. In the introduction Gregory MacDonald argues that theologies of universal salvation occupy a space between heresy and dogma. Therefore disagreements about whether all will be saved should not be thought of as debates between the orthodox and heretics but rather as in-house debates between Christians. The studies in this collection aim, in the first instance, to hear, understand, and explain the eschatological claims of a range of Christians from the third to the twenty-first centuries. They also offer some constructive, critical engagement with those claims.